Kegiatan Peningkatan Kebugaran Fisik Melalui Edukasi Pencegahan Nyeri Punggung Belakang pada Dewasa Muda di Pejagalan Jakarta Barat - Tjie Haming Setiadi; Susy Olivia; Nanang Wahyu; Dondie Dondie (Compromise Journal Community Proffesional Service Journal, 2024)
Physical fitness is explored in relation to muscle strength. Back pain is a musculoskeletal complaint that often occurs in productive young adults in today's digital era. The aim of the service activity is to increase knowledge regarding muscle strength training to prevent back pain and early detection of factors that cause back pain. The method of implementing the activity is screening for BMI, back pain, muscle endurance and education on back strengthening exercises. Educational and examination activities were carried out on Friday 10 November 2023 at 15.00-18.00 attended by 25 participants with 11 male participants and 14 female participants. The average age of service participants was 24.32 years, in the range of 20-28 years. There were 15 participants with overweight and obesity nutritional status. There were 18 participants who often experienced stiffness in their shoulders and back during activities. There were 22 participants who often experienced back pain, 14 participants had never done muscle strength training and 1 participant did exercise more than 5 times in 1 week. Health education is also carried out regarding the knowledge that there is no need to be afraid to move actively if the shoulder or back muscles are weak or tense. Participants are introduced to types of exercise as well as exercises to strengthen and stabilize the inner abdominal muscles (stomach), back and pelvis, as well as stretching exercises for the calf and hip muscles. and thighs.